NSRG-20. LONG-TERM SUPRATENTORIAL WHITE MATTER CHANGES AND COGNITIVE FUNCTION FOLLOWING CEREBELLAR TUMOUR RESECTIONS IN CHILDHOOD. Issue 2 (22nd June 2018) - Dorfer, Christian; Chocholous, Monika; Pletschko, Thomas; Kasprian, Gregor; Widmann, Christian; Slavc, Irene; Czech, Thomas
Abstract: INTRODUCTION: The cerebellum is connected to extensive regions of the cerebrum, and cognitive deficits following surgically treated cerebellar pilocytic astrocytomas (CPA) may thus be explained by distant cerebral white matter changes. Moreover, early cerebellar lesions could affect distal brain development, thereby influencing long term changes in brain structure and cognitive function. METHODS: We characterized supratentorial white matter changes and cognitive functions in 13 adult patients (f:6; m:7) (median age at time of testing 22.0 years) operated on a CPA in childhood (median age at surgery 7.4 years) and 13 matched controls. Cerebral white matter changes were evaluated using voxelwise statistical analysis of the FA data, which was carried out using TBSS (Tract-Based Spatial Statistics). TBSS projects all subjects' FA data onto a mean FA tract skeleton, before applying voxelwise cross-subject statistics. Neurocognitive functioning was tested regarding overall cognitive functioning, attentional performance, information processing speed, and cognitive flexibility. RESULTS: Neuropsychological results revealed significant group differences in overall IQ as denoted by the norm-corrected percentile (U= 176.00, z=3.162, p< .01, r= .587), with patients scoring at a mean of 48.6 +/- 29.14 versus controls at a mean of 85.25 +/- 15.45. Regarding white matter changes TBSS revealed significantly lower fractional anisotropy between subjects and controls within the corpus callosum and parts of the left frontal opercular white matter (FWE-corrected, p< .05). CONCLUSION: Our results show distant effects of cerebellar lesions on cerebral integrity, likely caused by a combination of neurodegenerative processes and perturbed neurodevelopment.